Peranan Humas Dalam Meningkatkan Kualitas Komunikasi Vertikal Di Dinas Kehutanan Provinsi Riau - Monica Mutiara Tinambunan (KOM & REALITAS SOSIAL, 2011)
The forestry official in Riau Province is a government instance that does the government official's house in forestry. One of the phenomenon that we can see in this official that connected to vertical communication is the less of that vertical communication between the leader and the subordinates and the contrary. The purpose of this observation is : 1.To know how is the role of public relations in increasing the quality of vertical communication in this forestry official. 2. To know the support factor of the Public Relations succeded in increasing the quality of vertical communication in this forestry official. 3.To know the barrier factor of Public Relations in increasing the quality of vertical communication in this forestry official. This observation uses a descriptive analysis method with a qualitative approach that give an emphasized to the way of looked, valuation or the emotion of an informan that I search as a data. The source of data consists of the primary data that directly found from the Public Relations and the employer of the forestry official in Riau Province. The result of this observation shows that : 1. The role of the PR is less than how it has to be in increasing the quality of vertical communication. 2.The support factor to make the Public Relations succeded the quality of vertical communication at the forestry official in Riau Province is the desire of Public Relations to study the Public Relations by themselves. 3. the barrier of Public Relations in increasing the quality of vertical communication at forestry official in Riau Province is the Public Relations is just focusing themselves at the general activity of Public Relations. Especially the external activity like documentation and publication. Otherwise, they left the internal activity.